The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.2478/intag-2014-0001
|View full text |Cite
|
Sign up to set email alerts
|

Field Validation of DNDC and SWAP Models for Temperature and Water Content of Loamy and Sandy Loam Spodosols

Abstract: A b s t r a c t. The objectives of the research were to: fulfil the preliminary assessment of the sensitivity of the soil, water, atmosphere, and plant and denitrification and decomposition models to variations of climate variables based on the existing soil database; validate the soil, water, atmosphere, and plant and denitrification and decomposition modelled outcomes against measured records for soil temperature and water content. The statistical analyses were conducted by the sensitivity analysis, Nash-Sut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…The Spearman's rank correlation coefficients for relationships between soil temperature and air temperature ranged from 0.78 to 0.82 (at P < 0.05) and from 0.73 to 0.76 (at P < 0.05) between treatments of CT and RT, respectively. These results also agreed with data obtained by Balashov et al (2014) and Licht and Al-Kaisi (2005).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The Spearman's rank correlation coefficients for relationships between soil temperature and air temperature ranged from 0.78 to 0.82 (at P < 0.05) and from 0.73 to 0.76 (at P < 0.05) between treatments of CT and RT, respectively. These results also agreed with data obtained by Balashov et al (2014) and Licht and Al-Kaisi (2005).…”
Section: Resultssupporting
confidence: 92%
“…Water-retention curves of undisturbed soil samples were measured by a pressure-plate apparatus at water potentials of −5, −20, −50, −100 and − 300 kPa (Soil Survey Laboratory Methods Manual 1996). A saturated hydraulic conductivity of undisturbed soil samples was measured using the lab method as published in Antal and Igaz (2006).…”
Section: Soil Sampling and Analysismentioning
confidence: 99%
“…Several studies have investigated the effectiveness of the DNDC model to access and predict GHG emissions and crop yields under different management practices and emissions scenarios in wheat fields and have demonstrated that the simulated results of DNDC are helpful in choosing best management practices to decrease nitrate leaching and N 2 O and NO emissions (Ludwig et al, 2011;Smith et al, 2013;Cui et al, 2014;Sansoulet et al, 2014). In addition, DNDC is also widely used and compared with other models to investigate the influence of future climate change and the application of advanced agricultural management measures to achieve good application results in barley fields (Abdalla et al, 2011;Smith et al, 2012;Cardenas et al, 2013;Balashov et al, 2014;Deng et al, 2015).…”
Section: Tablementioning
confidence: 98%
“…In terms of preferential flow, it cannot be limited by macropores as irregular wetting patterns within the soil matrices can also affect water flow (DEKKER & RITSEMA, 1996). Water and solute transport in heterogeneous and variably saturated soil matrices have been studied in the past several decades by numerous researchers (BALASHOV et al, 2014;HARDELAUF et al, 2007;HARTER & ZHANG, 1999;HOREL et al, 2015;TWARAKAVI et al, 2010). Preferential flow can greatly influence both water and solute movement through the soil, as it was found by several studies (e.g.…”
Section: Introductionmentioning
confidence: 93%